ISLAMISASI DAN PERTUMBUHAN INSTITUSI PENDIDIKAN ISLAM DI NUSANTARA - Alfurqan Alfurqan; Nurul Fajri; Deprizon Deprizon; Ajat Hidayat (UIN Imam Bonjol Padang, 2021)
This study attempts to examine the Islamization and growth of Islamic educational institutions in the archipelago, a discussion at the beginning of how Islam entered Indonesia, halaqah as the earliest scientific center in the archipelago, and how the support of the kings at that time for education. This study uses qualitative research methods. This study discusses the growth of Islamic educational institutions in Indonesia, beginning with the origin of the advent of Islam, the bearers of Islam and the channels of Islamization as well as the growth and development of Islamic educational institutions. The type of study used is library research by using literature study methods and historical approaches. The literature that is the main source of this study is literature including journal articles that discuss the history of Islam and education in Indonesia. Islam spread through the role of three great kingdoms, namely; Samudra Passai, Perlak and Darussalam. The three kingdoms played an important role in the growth and early development of Islamic education in Indonesia. The earliest manifestation of Islamic educational institutions in the archipelago was halaqah, halaqah was performed in the Palace Mosque, in the colonies where Muslim traders stopped at the port. The lessons given in various halaqah range from basic to advanced level.